Development of Website-Based Learning Media to Improve the Learning Outcomes of Fifth Grade Students - Suryani; Dede Suratman; Antonius Totok Priyadi; Siti Halidjah; Martono (Postgraduate, University of Mataram, 2026)
The rapid advancement of technology has accelerated the digitalization of learning, including the use of website-based learning media such as Google Sites. These media support audio-visual learning, increase student engagement, and have the potential to improve learning outcomes. Although SDN 07 Sedoya has received Chromebooks and tablets, their use has not been optimal due to limited teacher skills and knowledge. Therefore, this study aimed to develop website-based learning media and evaluate its feasibility, practicality, and effectiveness in improving fifth-grade students’ Indonesian language learning outcomes. The study employed the ADDIE development model and involved 25 fifth-grade students at SDN 07 Sedoya. Data were collected using questionnaires and learning outcome tests. The results indicated that the developed media were highly feasible, with validation scores of 96% for material, 95% for language, and 81% for media aspects. The practicality evaluation yielded a score of 4.0, indicating that the media were practical to use. Furthermore, the paired-samples t-test produced a significance value of 0.00 (p < 0.05), demonstrating that the website-based learning media significantly improved students’ learning outcomes. These findings suggest that the developed website-based learning media are feasible, practical, and effective for Indonesian language learning in elementary schools.